The international politics of space - Sheehan, Michael [ (Michael J.)] (London : Routledge, 2007)
The year 2007 will see the 50th anniversary of the Space Age, which began with the launching of Sputnik by the Soviet Union in October 1957. Since that time, the development of space technology has revolutionised many aspects of life on Earth, from satellite television to mobile phones, the internet and micro-electronics. It has also helped to bring about a revolution in the use of military force by the most powerful states. Space is crucial to the politics of the postmodern world. It has seen competition and cooperation in the past fifty years, and is in danger of becoming a battlefield in the next fifty. The International Politics of Space is the first book to bring these crucial themes together and provide a clear and vital picture of how politically important space has become, and what its exploitation might mean for all our futures. Michael Sheehan analyses the space programmes of the United States, Russia, China, India and the European Space Agency, and explains how central space has become to issues of war and peace, international law, justice and international development, and cooperation between the worlds leading states. It highlights the significance of China and India?s commitment to space, and explains how the theories and concepts we use to describe and explain space are fundamental to the possibility of avoiding conflict in space in the future. This ground-breaking book will be of great interest to students of international relations, space politics and security studies
1. Perceptions of space and international theory -- 2. Propaganda and national interest: scientific socialism and the Soviet space programme, 1957-69 -- The new frontier : US space policy, 1957-72 -- 3. International cooperation in space -- 5. European integration and space -- 6. Space as a force multiplier -- 7. Space control -- 8. Space, justice, and international development -- 9. India: security through space -- 10. China : the long march into space -- 11. Cooperation and competition in the post-Cold War era
Includes bibliographical references (p. [184]-230) and index
Keywords: International relations; Outer space -- Exploration -- International cooperation; Outer space -- Exploration -- Political aspects